Congenital Insensitivity to Pain With Anhidrosis: First Reported Case in Nepal - Sobin Pant; Dibij Adhikari; Prakash Pandey; Binit Bajracharya; Rizuna Sharma (Clinical Case Reports)
ABSTRACT Congenital insensitivity to pain with anhidrosis is a rare autosomal recessive disorder characterized by anhidrosis, self‐mutilation, and insensitivity to pain and temperature. While genetic testing confirms the diagnosis, it is not always feasible, making clinical recognition crucial in resource‐limited settings. Early diagnosis and a multidisciplinary approach help prevent complications like severe injuries, infections, and hyperpyrexia.